Farmers' Decision to Adoption of Modern Irrigation Systems Under Risk Condition: Application of Stochastic Efficiency With Respect to a Function Approach - Jahangirpour, Dorna; Zibaei, Mansour (Frontiers in Water, 2022)
To effectively tackle the issue of increasing irrigation water scarcity, farmers need to convert to ‎modern ‎irrigation systems with lower water-use while achieving higher yields and profitability. ‎Unlike the government ‎support to cover a proportion of irrigation modernizing costs by public ‎subsidies in Iran, the adoption rate is ‎low. This is due to farmer’s uncertainty about the trade-off ‎between benefits from yield improvement and the ‎added production costs. The historical gross ‎margin of barley, wheat, forage corn, and tomato under surface, ‎drip, permanent sprinkler, and ‎semi-permanent sprinkler irrigation systems was generated using simulation ‎and survey-based data ‎for yield and published data for costs and prices over a five-year period (2009–2015). ‎‎The ‎stochastic dominance and stochastic efficiency with respect to a function (SERF) approaches were ‎used ‎to evaluate the risk-efficiency of various irrigation systems for main ‎crops in the Bakhtegan ‎Basin. Estimating certainty equivalent (CE), we ranked irrigation alternatives at ‎different absolute ‎risk-aversion coefficient (ra) levels. The findings show that drip irrigation systems for ‎forage corn ‎and tomato have higher CE values at all levels of absolute risk aversion coefficient, however the ‎‎preferred system for barley and wheat varies with ra. Moreover, estimated risk premiums revealed ‎that risk-‎neutral farmers would pay to move from surface system to more efficient systems, ‎whereas, risk-averse ‎farmers need to be paid to have the tendency to change their irrigation system‎. ‎The important policy implication of these results is that risk premiums can consider justifying ‎‎subsidy allocation in a manner that induces farmers to more risk-efficient irrigation systems.‎